2002
DOI: 10.4049/jimmunol.169.11.6522
|View full text |Cite
|
Sign up to set email alerts
|

Production of Type I IFN Sensitizes Macrophages to Cell Death Induced byListeria monocytogenes

Abstract: Type I IFNs (IFN-α/β) modulate innate immune responses. Here we show activation of transcription factor IFN regulatory factor 3, the synthesis of large amounts of IFN-β mRNA, and type I IFN signal transduction in macrophages infected with Listeria monocytogenes. Expression of the bacterial virulence protein listeriolysin O was necessary, but not sufficient, for efficient IFN-β production. Signaling through a pathway involving the type I IFN receptor and Stat1 sensitized macrophages to L. monocytogenes-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
167
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(186 citation statements)
references
References 72 publications
16
167
3
Order By: Relevance
“…This late tyrosine phosphorylation is similar to challenges with other bacteria (e.g. Listeria monocytogenes) that do not induce IFN synthesis through direct engagement of an IFN-inducing TLR (23). Consistently, Stat1 activation proceeded independently of MyD88 and TLR2, TLR4, and TLR9 signaling, as shown by GAS infection of BMDMs from MyD88 Ϫ/Ϫ (Fig.…”
Section: Gas Activates Inflammatory Signaling Independently Of Tlr2 supporting
confidence: 54%
See 2 more Smart Citations
“…This late tyrosine phosphorylation is similar to challenges with other bacteria (e.g. Listeria monocytogenes) that do not induce IFN synthesis through direct engagement of an IFN-inducing TLR (23). Consistently, Stat1 activation proceeded independently of MyD88 and TLR2, TLR4, and TLR9 signaling, as shown by GAS infection of BMDMs from MyD88 Ϫ/Ϫ (Fig.…”
Section: Gas Activates Inflammatory Signaling Independently Of Tlr2 supporting
confidence: 54%
“…The IFN production did not require the presence of the GAS-encoded cytolysins SLO and SLS. This finding is surprising, since during infections with other Gram-positive bacteria, either the cytolysin itself or cytolysin-mediated cytoplasmic escape of bacteria from phagocytic vesicles was implicated in triggering IFN production (12,(23)(24)(25). However, the requirement for IRF3 in the IFN production suggested that other aspects of the GAS-induced IFN production resembled the well established TBK1/IRF3 signaling pathway.…”
Section: Bacterial Pathogens Are Recognized By the Innate Immune Systcontrasting
confidence: 39%
See 1 more Smart Citation
“…Surprisingly, three recent studies indicate that type I IFN signaling may actually decrease host resistance against L. monocytogenes infection (16 -18). The mechanisms underlying these detrimental effects are presently unknown, but may be related to the proapoptotic effects of Listeria-induced type I IFN (17)(18)(19).…”
mentioning
confidence: 99%
“…Type I IFNs were shown to increase lymphocyte apoptosis (53,59,60), enhance macrophage cell death (61,62), antagonize IFN-g signaling by downregulating the IFNGR on APCs (63), inhibit neutrophil migration (64), and reduce the production of protective IL-12 and TNF-a (58,59). Together, these findings suggest that the bacteriuminduced type I IFNs can modulate multiple protective mechanisms to impair survival of the infected host.…”
Section: Listeriamentioning
confidence: 99%